2016
DOI: 10.5005/jp-journals-10045-0040
|View full text |Cite
|
Sign up to set email alerts
|

Cost Burden of Dengue Fever in a Rural Ramanagara District of Karnataka State

Abstract: Introduction Dengue fever is an arboviral disease caused by dengue virus, which is a single-stranded RNA virus and belongs to family Flaviviridae. Dengue fever (DF) has emerged as a global public health problem in recent years. The problem has become hyperendemic in many urban, peri-urban and rural areas, with frequent epidemics South-East Asia is one of the regions with highest risk of DF and accounts for 52% of the worldwide risk. In India, according to World Health Organization, 70.8% of the total health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
2
3
Order By: Relevance
“…The total medical cost of dengue and chikungunya patients in the present study was higher than that reported in the earlier study from Surat[ 31 ] which was USD 14.8 (IQR 7.3–65.9)/INR (IQR 465–4194) and the average cost was USD (86.9 ± 170.7)/INR (5530 ± 10837). Another study from Surat[ 29 ] reported a direct medical cost of USD 439.44/INR 20407 which was similar to our study.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…The total medical cost of dengue and chikungunya patients in the present study was higher than that reported in the earlier study from Surat[ 31 ] which was USD 14.8 (IQR 7.3–65.9)/INR (IQR 465–4194) and the average cost was USD (86.9 ± 170.7)/INR (5530 ± 10837). Another study from Surat[ 29 ] reported a direct medical cost of USD 439.44/INR 20407 which was similar to our study.…”
Section: Discussioncontrasting
confidence: 81%
“…The total indirect cost of dengue and chikungunya patients in the present study was higher than that reported in the earlier study from Surat[ 29 ] which was USD 146.13/INR 6786. In other studies, the average indirect cost per household for treatment of dengue reported from Karnataka was INR 1540.65,[ 31 ] Haryana was INR 1840,[ 32 ] and from Vietnam was USD 28.7/INR 1693[ 41 ] which was less than our present study. The total direct and indirect cost of dengue and chikungunya patients was higher than the earlier reported study from Karnataka (INR 11278),[ 31 ] Haryana (INR 11563),[ 32 ] and Vietnam (USD 61.3/INR 3720).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The findings were similar to the study conducted by Kumar N et al, in the rural district of Karnataka & found that 77.6% of households used their savings to pay for dengue care, 18.4% borrowed money from friends and family to pay for hospital bills, and the remaining 3% used their health insurance as a financial tool. 15…”
Section: Discussionmentioning
confidence: 99%